ปัจจัยที่ส่งผลต่อการตัดสินใจเลือกใช้บริการร้านปิ้งย่างเกาหลีในจังหวัดนครปฐม - ดาวเรือง คุณากร; วิชากร วิชากร (Journal of Buddhist Education and Research (JBER), 2023)
This research aimed to study: 1) level marketing mix and service decisions to choose Korean grill restaurants; 2) to compare service decisions to choose Korean grill restaurants, classified by personal factors; and 3) to present the relationship between marketing mix and service decisions to choose Korean grill restaurants. This research employs a quantitative method. The tool of this research is a questionnaire. Data were collected from 400 persons who chose Korean grills restaurants in Nakhon Pathom province, by nonprobability sampling and purposive sampling. The statistics used in the research were frequency, percentage, mean, standard deviation, t-test, F-test, and Pearson’s correlation analysis. The results of the research showed that 1) factors of marketing mix and service decision to choose Korean grills restaurants were at a high level with an average of 4.07 and 4.05 and a standard deviation of .531 and .533, and 2) personal factors by sex, age, education, income, and occupation had no effect on service decision to choose Korean grills restaurants at a statistically significant of .05, and 3) marketing mix factors by product, price, place, promotion, people, process, and physical evidence have a relation to service decision to choose Korean grills restaurants in Nakhon Pathom province at a statistically significant of .01, at the value R2=.862. There is a high relationship